Offering Sexual Health Fairs to Supplement Existing Sex Education Programs: An Evaluation of Adolescent Students' Knowledge Needs - Wood, Eileen; Senn, Charlene Y.; Desmarais, Serge; Verberg, Norine (Alberta journal of educational research, 2000)
A health fair called Choices Not Chances has been designed by the public health nurses in a southern Ontario city to increase the knowledge of young high school students about sexual health and healthy relationships. Our purpose in designing this study in cooperation with the public health nurses ivas to assess the existing level of knowledge among grades 9 and 10 students to determine if the content presented through this fair was appropriate for these students. Forty-five grades 9-10 students completed one survey during class time in their sex-segregated physical education class. Our findings show that although students had basic knowledge about STDs, anatomy, and pregnancy prevention, their knowledge of healthy communication and behavior in relationships was much less developed, which may put students at risk of becoming involved in unsafe sex and abusive relationships. Overall, the health fair appears to provide a valuable supplement for sex education.